DAMPAK DISAIN MANAJEMEN DAN PROSES MANAJEMEN TERHADAP KUALITAS PADA PERUSAHAAN MANUFAKTUR DI JAKARTA - Yolanda M. Siagian (Media Riset Bisnis & Manajemen, 2003)
Design management and process management are two important elements of total quality management (TQM) implementation. They are drastically different in their targets of improve-ment, visibility, and techniques. The goal of the research to establish a framework identifying the synergistic linkages of design and process management to operational quality outcomes during the manufactunng process (internal quality) and upon the field usage of the products (external quality). Through a study of quality practices in manufacturing plants firm multiple industhes, empirically demonstrate that both design and process management effort have an equal positive impact on internal quality outcomes such as scrap, rework, defect, perfor-mance, and external quality outcomes such as complaints, warranty, litigation, market share. Finally, the results also suggest that organizational learning enables mature TQM firms to implement both design and process efforts more rigorously and their synergy helps these firms to attain better quality outcomes.